Pattern of use and determinants of return visits at community or Mohalla clinics of Delhi, India - Tanisha Agrawal; Shubhro Bhattacharya; Chandrakant Lahariya (Wolters Kluwer Medknow Publications, 2020)
Background: Mohalla or Community Clinics of Delhi, India, have made primary care accessible, equitable, and affordable for women, elderly, and children in the underserved areas. Objectives: To understand the population subgroups which use these clinics and to analyze why people use these facilities and the determinants of the return visits for health seeking. Materials and Methods: This was a community-based cross-sectional study, with primary data collection from 25 localities across Delhi. A pretested semi-structured interview schedule was used for data collection. Two regression models were used for data analysis: a linear probability model to understand the factors contributing to the use of these clinics and a probit regression model to understand the determinants of return visits to these facilities. Results: Four hundred ninety-three ever-married women residing in study settings were included. The age of beneficiaries, marital status, distance from the clinics, and awareness about the services were found to be positively associated with the use of Mohalla Clinics. The proximity to households, waiting time at clinics, interaction time with the doctor, perceived performance of doctor, and effectiveness of treatment influenced the decision on a return visit for care seeking. Conclusions: Improved information on service provision, proximity to the facility, assured provision of doctors and laboratory services, and increased patient-doctor interaction time have the potential to increase the use and return visits to these Community or Mohalla Clinics. The lessons from this study can be used to design government primary health-care facilities in urban settings, for increased use by the target populations.